STUDI SIMULASI METODE DELIQUIFIKASI PADA SUMUR GAS DENGAN METODE DUAL-TUBING LIFTING - Ahmad Firdaus, Imam
Deliquification is a solving method for liquid loading in gas well which alaways happen when the gas well have pressure and temperature depletion. The depletion of pressure trigger the gas condensation in gas well which is the condensate acumulated and blocks the gas flow in bottom hole. Another source of liquid is from aquifer or water production zone. This condition will decrease the performa reservoir and make it no stable. Dual-tubing lifting is one of deliquification method which is recomended in this study. This method is developed and validated by investigate the influence of sensitivity in tubing?s geometri and pressure drop. This sensitivity has a function to find the optimal configuration of tubing?s parameter which can be effective in liquid lifting to control the liquid loading in gas well. This method is optimized by the different multi phase flow regime of each tubing. In small tubing we have to design slug flow to get large number of liquid fraction dellivery. In bigger tube we have to design mist or transition flow to get optimum gas dellivery which is gas is primary product in this well. This optimizing process is helped by PIPESIM Simulator which is running in steady state condition. The result of this simulation is the optimum configuration of tubing which get the optimal liquid lifting.